Learning Strategies in Al-Qur'an-Hadith Education within Islamic Religious Education Programs in Schools - Lailatul Qomariah; Ainur Rofiq Sofa; Kustiana Arisanti; Ahmad Khumaidi; Abd Aziz; Imam Bukhori (Education and Sociedad Journal, 2026)
This study explores learning strategies employed in Al-Qur'an-Hadith education within Islamic Religious Education (PAI) programs in schools. The research aims to identify instructional approaches used by teachers, examine their implementation in classroom settings, and analyze their contribution to students’ understanding of Qur’anic and Hadith teachings. Using a qualitative case study approach, data were collected through classroom observations, in-depth interviews with teachers and students, and analysis of relevant educational documents. The findings reveal that teachers utilize a combination of lecture, discussion, memorization, contextual learning, collaborative learning, and technology-assisted strategies to facilitate students’ comprehension of religious texts. The integration of active learning methods encourages student participation, critical thinking, and the practical application of Islamic values in daily life. Furthermore, the effectiveness of learning strategies is influenced by teacher competence, learning resources, school support, and students’ learning motivation. The study concludes that diverse and student-centered learning strategies enhance the quality of Al-Qur'an-Hadith instruction by promoting both cognitive understanding and character development. These findings contribute to the development of more effective pedagogical practices in Islamic Religious Education and provide recommendations for improving the teaching and learning of Al-Qur'an-Hadith in contemporary school settings.